Baseline evaluation of environmental quality in urban underground tunnel - Tan, Sok Keng (2016)
Currently, Singapore has three urban underground roads including MCE, KPE and CTE. By 2020, NSE will be the 4th underground expressway in Singapore. Tunnel environmental quality baseline evaluation was set as the objective of this Final Year Project. As high volume of vehicles is passing through KPE daily, it is important to understand the conditions of the tunnel so as to further develop maintenance strategies to continue to provide a better environment for road users. Especially when the NSE will be completing in 2020, this study could be used as a reference to forecast the environmental quality as well as finding suitable solutions in providing a safer environment for road users. Data was collected from 30 LTA monitoring sensors throughout the tunnel. However, only 10 sensors were functional for all three parameters which are concentration of CO, temperature and visibility coefficient. Out of the three different type of sensors, the CO detector is the most unstable as it has short lifespan due to the working mechanisms. A typical weekday (Tuesday, Wednesday, Thursday) and weekend (Saturday and Sunday) was chosen for 24-hour analysis as well as analysis along Southbound (SB) and Northbound (NB). Collection of data was also done at two different locations (5.35km and 6.65km SB) during tunnel closure on 16th November 2015 in which data recorded was used for comparison against LTA data at the same location and timing. The temperature was highest at 36oC on a typical weekday and 35.7oC on a typical weekend. Visibility is the lowest in the morning at 169m. By comparing the results with the PIARC standard. The CO is usually less than 10ppm which complied with the standards while the visibility is low at 169m which exceeds the guideline of 200m recommended by PIARC. The air was carried forward along in the direction of traffic flow through the tunnel. The temperature, concentration of CO and visibility are worse at the exit of the tunnel compared to the conditions near the entrance. The comparison between NTU and LTA data showed similar trends with small percentage of difference in values. The difference in temperature ranges from 0.5% to 4.5%. It is important to provide a safer environment for the road users at an energy efficiency level to be sustainable. This project provides an overview of the environmental quality of the KPE tunnel which could aid in future studies on improving the conditions of the tunnel environment.